2022
DOI: 10.3390/antiox11101984
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Reveals Nutritional Diversity among Six Coarse Cereals and Antioxidant Activity Analysis of Grain Sorghum and Sweet Sorghum

Abstract: Coarse cereals are rich in dietary fiber, B vitamins, minerals, secondary metabolites, and other bioactive components, which exert numerous health benefits. To better understand the diversity of metabolites in different coarse cereals, we performed widely targeted metabolic profiling analyses of six popular coarse cereals, millet, coix, buckwheat, quinoa, oat, and grain sorghum, of which 768 metabolites are identified. Moreover, quinoa and buckwheat showed significantly different metabolomic profiles compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…To further investigate the potential mechanisms of the antioxidant properties of the strain FGM, we examined the expression profiles of metabolite levels in the FCFS, performing correlation analyses to better understand specific metabolites. Due to the differences in metabolites, and the fact that antioxidant active components occurring differently in each strain, the metabolome has become an effective tool for analyzing metabolite accumulation patterns and has been used for nutritional analysis of many substances 44 . In the quantitative N300 assay performed on the FCFS, a total of 156 metabolites were detected, and 46 metabolites (12 up-regulated and 34 down-regulated) among them were significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the potential mechanisms of the antioxidant properties of the strain FGM, we examined the expression profiles of metabolite levels in the FCFS, performing correlation analyses to better understand specific metabolites. Due to the differences in metabolites, and the fact that antioxidant active components occurring differently in each strain, the metabolome has become an effective tool for analyzing metabolite accumulation patterns and has been used for nutritional analysis of many substances 44 . In the quantitative N300 assay performed on the FCFS, a total of 156 metabolites were detected, and 46 metabolites (12 up-regulated and 34 down-regulated) among them were significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics has been efficiently used to analyze the type, content and accumulation pattern of metabolites [20], and also can be utilized in the analysis of nutritional compounds for many plants [21]. For example, a widely targeted metabolic profiling analysis was performed to investigate nutritional diversity among six coarse cereals including millet, grain sorghum, oat, coix, buckwheat and quinoa [18]. In another work, the widely targeted metabolomics-based approach was used to reveal the nutritional components of black, red, glutinous, and common white rice [22].…”
Section: Comparative Analysis Of the Important Nutrients And Anti-nut...mentioning
confidence: 99%
“…Metabolomic variations were investigated among six important species of Poaceae with a total of 17 cultivars, including wheat, maize, rice, sorghum, foxtail millet, and broomcorn millet based on the UPLC-ESI-MS/MS system [1]. Analysis of the accumulation patterns of common nutritional metabolites among six coarse cereals found that the accumulation of carbohydrates follows a conserved pattern [18].…”
Section: Introductionmentioning
confidence: 99%
“…Millet is rich in trace elements selenium, iron and a variety of vitamins, and has the effect of preventing insomnia and cardiovascular and cerebrovascular atherosclerosis; Oat is rich in saponins and β-glucan, which has special effect on reducing blood lipids. Buckwheat is rich in bioflavonoids, which can significantly soften blood vessels and regulate blood lipids and blood sugar ( Zhao et al, 2022 ). Compared to main crops and model plants, research on the formation mechanism, development process, and regulation mechanism of environmental adaptability of special metabolic components of coarse grain crops is insufficient.…”
mentioning
confidence: 99%
“…Millet is rich in trace elements selenium, iron and a variety of vitamins, and has the effect of preventing insomnia and cardiovascular and cerebrovascular atherosclerosis; Oat is rich in saponins and β-glucan, which has special effect on reducing blood lipids. Buckwheat is rich in bioflavonoids, which can significantly soften blood vessels and regulate blood lipids and blood sugar (Zhao et al, 2022). Compared to main crops and model plants, research on the formation mechanism, development process, and regulation mechanism of environmental adaptability of special metabolic components of coarse grain crops is insufficient.This Research Topic aimed to explore recent developments in this area with a focus on the genetic basis of special chemical compositions, nutritional structures, tissue developments, and biological or abiotic adaptability of these coarse grain crops through forward or reverse genetic experiments.Sorghum is one of the world's most important cereal crops, an important source of animal feed worldwide and an increasingly important biofuel feedstock.…”
mentioning
confidence: 99%